Letter from the Secretary of the Interior transmitting an agreement with the Nez Percé tribe in Idaho : together with the report of the commissioner appointed to negotiate with said Indians, and a draft of a bill to confirm and ratify said agreement (Senate executive document (United States. Congress. Senate), 1894)
Documents and reports related to a cession of surplus lands by the Nez Percé tribe.